2014
DOI: 10.1093/carcin/bgu017
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 selectively promotes the metastasis of colorectal carcinoma cells with impaired Socs3 expression via the STAT5 pathway

Abstract: Interleukin-23 (IL-23) is a conventional proinflammatory IL related to colorectal carcinoma (CRC). The signal transducer and activator of transcription (STAT) and suppressors of cytokine signaling (Socs) molecules, respectively, serve as agonists and antagonists of IL-23-associated inflammation. However, it remains unknown whether IL-23 directly affects CRC metastasis. In this study, we measured the metastasis of several human CRC cell lines stimulated by IL-23 in vitro and in vivo. Interestingly, the prometas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 26 publications
2
46
0
Order By: Relevance
“…Recent investigations have demonstrated that IL-23 plays a role in tumorigenesis and acts as a potential marker of the invasion process2425262728. Here, we found that IL-23 was highly expressed in samples from OC patients, especially with the progression of malignancy.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Recent investigations have demonstrated that IL-23 plays a role in tumorigenesis and acts as a potential marker of the invasion process2425262728. Here, we found that IL-23 was highly expressed in samples from OC patients, especially with the progression of malignancy.…”
Section: Discussionsupporting
confidence: 48%
“…However, the role of IL-23 in cancer is not consistent and is occasionally controversial. In some studies, IL-23 displays anti-tumour and anti-metastatic effects, whereas in others, it promotes proliferation and metastasis202122232425262728. Therefore, the elucidation of how IL-23 impacts cellular homeostasis is urgent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation-mediated down-regulation of SOCS3 has been shown to be related to the abnormal cell growth and migration in same disease, which is mediated through loss of regulation of JAK/STAT and FAK signaling [88]. Loss of SOCS3 function results in elevated STAT5 activation leading to higher metastasis in colorectal carcinoma patients [89]. SOCS3 expression is elevated in chronic myeloid leukemia (CML) and confers resistance to interferon α (IFNα) treatment [90] indicating that expression of SOCS3 is associated with disease progression.…”
Section: Socs Proteins In Rtk Regulated Diseasesmentioning
confidence: 99%
“…SOCS3 downregulation in concert with CXCL1 and CXCR4 induction and IGFBP3 suppression could produce additive or synergistic motogenic signaling. Decreased SOCS3 expression also identifies a subset of PCa patients with more aggressive disease [54,55] and has a pro-metastatic role in other cancers [56,57]. DDX58 encodes an interferon-inducible mediator of inflammatory and antiviral responses associated with the NFkB and Akt pathways, and can activate or inhibit tumor cell proliferation in a context dependent manner [58,59]; the impact of HGF induction of DDX58 on PC3M invasiveness is unclear.…”
Section: Analysis Of Hgf Motogenic Signaling By Gene Expression Profimentioning
confidence: 99%